Effect of beta-glucan on oxidative stress, inflammation, hormonal and histopathological changes in dehydroepiandrosterone-induced polycystic ovary syndrome - Yuce, H.; Turkmen, N. Basak; Aydin, M.; Taslidere, A.; Ozek, D. Askin; Senkal, S.; Unuvar, S. (Taylor & Francis Ltd, 2026)
Beta-glucans (beta TGs) are a class of dietary fibers and biologically active polysaccharides derived from natural sources, known for their diverse bioactive properties. Their documented effects include anti-tumor, anti-inflammatory, prebiotic, anti-obesity, anti-allergic, anti-microbial, antiviral, anti-osteoporotic, and immunomodulating activities. Despite these well-established benefits, the role of beta TG in dehydroepiandrosterone (DHEA)-induced polycystic ovary syndrome (PCOS) remains largely unexplored. This study investigated the protective effects of beta TG treatment on PCOS and its potential to reverse PCOS-induced changes. Female Sprague-Dawley (SD) rats were randomly divided into four groups (n = 8 each): control, PCOS, PCOS+beta TG, and beta TG. We assessed biochemical markers related to oxidative stress, antioxidant status, inflammation, cytokines, and hormone levels. Additional analyses included immunohistochemistry and histopathology. Membrane array analysis was used to profile growth factors, cytokines, and chemokines. However, beta TG normalized deviations in the estrous cycle caused by PCOS and positively affected the reproductive system (p < 0.05). It also reduced the inflammatory response in PCOS rats by decreasing inflammatory cytokines (p < 0.05). Furthermore, oxidative stress was significantly reduced, and antioxidant enzyme activities were markedly elevated in the beta TG group (p < 0.05). Histopathological alterations were prevented by beta TG, which also induced the expression of essential proteins such as beta-nerve growth factor (bNGF), tissue inhibitor of metalloproteinase-1 (TIMP-1), Agrin, cytokine-induced neutrophil chemoattractant-1 (CINC-1), brain-derived neurotrophic factor (BDNF), and basic fibroblast growth factor (FGF-2/bFGF) (p < 0.05). In conclusion, beta TG treatment effectively protects against oxidative stress, inflammation, hormone imbalance, and histopathological damage in ovarian tissue caused by PCOS.
Keywords: Antioxidants; beta-glucan; dehydroepiandrosterone; inflammation; oxidative damage; polycystic ovary syndrome